Development of an MPS Code for Corium Behavior Analysis: 3D Alloy Melting - Lijun Jian; Peng Yu; Jie Pei; Xiao Zeng; Yidan Yuan (Science and Technology of Nuclear Installations)
The moving particle semi-implicit (MPS) method as a Lagrangian method is attracting increasing attention in severe accident analysis. In this paper, we developed an MPS code for the corium behavior analysis with several additional models added: an improved heat transfer model to improve the calculation between different materials, an enthalpy-based viscosity model to realize a smooth transition of viscosity at the solid-liquid interface, and a surface tension model for better simulation of surface shape. Validation of the developed simulation approach is carried out on a classical water column collapse example. The development of the heat transfer model is validated by the example of a one-dimensional semi-infinite plate. A comprehensive example of the melting of “Wood’s alloy” is carried out to verify the capacity of MPS method in the simulation of melting and expansion. The simulation results are in good agreement with the experimental results, which indicates that MPS method promises well in the field of severe accidents.